The Language of Cartography in Anne Enright’s Writings - Piñeiro, Aurora (ABEI Journal, 2023)
The aim of this article is to analyse the novel Actress (2020) by Anne Enright from the perspective of a twofold notion of literary mapping: firstly, the author’s role as a cartographer, when she adopts and adapts the conventions of Bildungsroman to draw the outline of a life and when the lexicon chosen for this task is imbued with the language of landscape and thus creates an imagery which may articulate a literary territory of her own or a geography of affects. And secondly, when the reader or critic exacts a map from several literary work(s) by the same writer, and this representation enables an additional reading of the text or set of texts. Although the novel Actress will remain the axis of the present analysis, for a larger mapping of Enright’s geography of affects and, in particular, her representation of motherhood, references to her non-fiction and short fiction writings will be necessary. In particular, her lecture “Maeve Brennan: Going Mad in New York” (2019) and fragments from her essay collection Making Babies (2004) will be incorporated. When it comes to her short fiction, “Night Swim” (2020) will be the story in focus. All these texts are thematically related and most of them are chronologically close but, more significantly, they incorporate cartographic imagery as a defining trait when it comes to the exploration of motherhood, which is viewed from an anti-essentialist perspective and with different degrees of the conciliatory.